Cluster Key Competences - Curriculum Reform: Synthesis Report on Peer Learning Activities in 2007 - Saavala, Tapio (Education and Training 2010, 2008)
This report takes stock of the work of the Cluster 'Key Competences and Curriculum reform', established within the 'Education and Training 2010 work programme1. Its remit is to assist Member States with the implementation of the Recommendation on Key Competences for lifelong learning, adopted in December 20062.The Cluster has undertaken three Peer Learning Activities (PLAs) in Belgium (Flanders), Hungary and Greece, and a number of meetings in Brussels have taken place to plan and evaluate these activities. The focus of these three PLAs has been on the implementation of key competences and in particular the cross-curricular or transversal key competences (learning to learn, social and civic, initiative taking and entrepreneurship, cultural awareness and expression). Member States' experts have looked into the policies and measures in national contexts that are needed to enable schools and other learning organisations to support the development of key competences among young people.While the focus has mainly been on school policies, all PLAs have looked at them in the context of the lifelong learning strategy of the country. This report gives an overview of the PLAs undertaken in three countries, and presents the conclusions and recommendations deriving from these PLAs that are common to all and thus transferable.Moreover, the report gives examples on how the host countries are applying theseprinciples within their specific contexts.
Published: Government Report
Keywords: Belgique; Europe; Grèce; Hongrie; compétence; éducation civique